2010
DOI: 10.1097/maj.0b013e3181cda0e3
|View full text |Cite
|
Sign up to set email alerts
|

Carbonic Anhydrase I, II, and VI, Blood Plasma, Erythrocyte and Saliva Zinc and Copper Increase After Repetitive Transcranial Magnetic Stimulation

Abstract: Introduction-Repetitive transcranial magnetic stimulation (rTMS) has been used to treat symptoms from many disorders; biochemical changes occurred with this treatment. Preliminary studies with rTMS in patients with taste and smell dysfunction improved sensory function and increased salivary carbonic anhydrase (CA) VI and erythrocyte CA I, II. To obtain more information about these changes after rTMS, we measured changes in several CA enzymes, proteins, and trace metals in their blood plasma, erythrocytes, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 189 publications
1
6
0
Order By: Relevance
“…Repeat stimulation (one to six applications) in this region induced a report of total absence of phantosmia (an intensity decrease of 50%–100%). Associated with this decrease changes in carbonic anhydrase I, II and VI and in zinc and copper similar to those measured in CUP were also reported [ 167 ].…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Repeat stimulation (one to six applications) in this region induced a report of total absence of phantosmia (an intensity decrease of 50%–100%). Associated with this decrease changes in carbonic anhydrase I, II and VI and in zinc and copper similar to those measured in CUP were also reported [ 167 ].…”
Section: Resultssupporting
confidence: 84%
“…In the patient in whom phantosmia inhibition persisted for 20 days phantosmia intensity increased after this period but only to about 60% of pre stimulation intensity after nose blowing and did not increase further in intensity with any physiological maneuver. Significant increases in carbonic anhydrase I, II and VI occurred in blood plasma, erythrocytes and saliva, respectively, and in plasma, erythrocytes and saliva zinc and copper measured after rTMS consistent with the phantosmia decrease in each patient [167]. Repeat stimulation was not performed in either patient.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…rTMS has been used with some success to treat the clinical manifestations of patients with Parkinson's disease, resulting in improved motor performance, elevation of serum dopamine, and improved smell and taste functions [158161]. It is not known whether changes in the copper levels at a systemic level are a reflex of changes in brain levels of copper or whether the improvement observed in patients with Parkinson's disease and other neurological disorders after rTMS is due, at least in part, to modifications in the copper levels.…”
Section: Copper-related Therapiesmentioning
confidence: 99%
“…On the other hand, in a study of patients with smell dysfunction, Henkin et al [ 158 ] reported that, after repetitive transcranial magnetic stimulation (rTMS), patients had increased copper concentrations in the plasma, erythrocytes, and saliva, showing that rTMS can produce changes in copper homeostasis. rTMS has been used with some success to treat the clinical manifestations of patients with Parkinson's disease, resulting in improved motor performance, elevation of serum dopamine, and improved smell and taste functions [ 158 161 ]. It is not known whether changes in the copper levels at a systemic level are a reflex of changes in brain levels of copper or whether the improvement observed in patients with Parkinson's disease and other neurological disorders after rTMS is due, at least in part, to modifications in the copper levels.…”
Section: Copper-related Therapiesmentioning
confidence: 99%